GAMBARAN STATUS GIZI LANSIA DI WILAYAH BINAAN PRODI NERS STIKes SANTA ELISABETH MEDAN - Endang Junita Sinaga; Lindawati Simorangkir (Elisabeth Health Jurnal, 2019)
Nutirional methods of the elderly is most important. Changes in body function effect to concumption and absortion of nutrients. The elderly with nutritional problems, it is necessary to cure and prevent complications from the disease. The most problems often are is malnutrion and obesity, it caused due to changes in diet and activities after retirement. Goals : This study aims to determine the description of the nutritional status of the elderly in the Nurse Study Program area of STIKes Santa Elisabeth Medan Method : The present study is descriptif to asses the nutritional status of the elderly Gerontik Ners Nursing Area STIKes Santa Elisabeth Medan using Body Mass Index (BMI) by measuring body weight and height in 30 elderly people. Results: The results showed that the majority of elderly people in the Elderly category (60- 74) 56.4%, the elderly who had gout acid comorbidities were 63.3% and over nutrition status 53.4%. Conculsion : From the results of the study it was found that the majority of the elderly experienced over nutrition 53.4%, based on the study suggested that the Gerontik Nursing group could provide optimum for the elderly. optimum nutrition for the elderly.